Aplikasi Strategic Planning dalam Perencanaan Pembangunan Kabupaten Fakfak Propinsi Irian Jaya - Keban, Yeremias T (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1998)
To date, there have been no regional development theories regarded as the most appropriate and valid in guiding and determining regional measures. Moreover, Indonesia has a very specific geographical, social, cultural and political backgrounds which could potentially complicate and constrain the development efforts. Such diversities and lack of valid regional theories require an innovative thought in regional development intervention. The application of Strategic Planning as an academic exercise in the context of regional development in Kabupaten Fakfak is an innovative alternative to overcome such complexities. Through the Strategic Planning approach, ten strategic sectors have been identified. Those sectors need to be incorporated into and developed in the Kabupaten longterm planning.